Macular corneal dystrophy related to novel mutations of CHST6 in a Chinese family and clinical observation after penetrating keratoplasty - Dewei Li; Le Tian; Xiaochuan Wang; Min Chen (BMC, 2021)
Abstract Background Macular corneal dystrophy (MCD) is a rare corneal stromal dystrophy with bilateral progressive vision loss. The pathogenic gene of MCD is carbohydrate sulfotransferase 6 (CHST6). Herein, we report a novel missense mutation and a rare exon deletion mutation in the CHST6 gene in a Chinese family with MCD. Methods Genomic DNA was extracted from the peripheral blood, and next generation sequencing was used to analyse the gene sequence. The pathogenic mutations were identified in all affected family members. The proband successively received binocular penetrating keratoplasty (PKP), and the corneas were examined by histopathology and colloidal iron staining to prove the diagnosis. A long-term follow-up was made to observe the changes after PKP. Results Genetic analysis demonstrated hemizygous mutations in the proband, including a novel c.520A>C (p.K174Q) missense mutation and a rarely reported exon 3 deletion mutation, which were co-segregated with the MCD phenotypes in the pedigree. The positive colloidal iron staining confirmed the diagnosis of MCD in the proband. However, the clinical phenotype and pathological manifestation of both eyes were different from each other because of complicated keratitis in the left eye. During the nine years of follow-up, visual acuity was improved significantly, and the cornea was transparent without rejection and postoperative recurrence in both eyes. Conclusions The novel hemizygous mutations were thought to contribute to the loss of CHST6 function, which induced typical clinical and pathological features of MCD. PKP was an effective treatment for MCD.